Assessment Of Human-Wildlife Conflict And Its Implication For Conservation at sundarpur, Udayapur, Eastern Nepal - Aryal, Chandramani; Pokharel, Manoj (Tribhuvan University Journal, 2019)
This study was carried out to document the prevailing situation of human-wildlife conflict in Sundarpur of Udayapur district, Nepal where significant numbers of sloth bear along with other troublesome wildlife species occur. Data about conflict and people's perception towards wildlife conservation was collected using household surveys supplemented by key informant interviews and direct observation method. Monkeys (93%) and elephants (86%) were found to be major animals involved in conflict mostly resulting into crop raiding, which was the major form of conflict as reported by (95%) of respondents. Livestock depredation cases were mostly by common leopard (84%) and sloth bear was involved in majority of human attack cases (90%). According to respondents, the trend of conflict was found to be increasing for elephants (63%) and monkeys (73%) while it was found to be decreasing for sloth bear (64%), wild boar (85%), and leopard (46%), where people believed natural attraction of wildlife towards crops/livestock to be the major driving factor of conflict. Despite the prevalence of conflict most of the respondents showed positive attitude towards wildlife conservation in Sundarpur. This implies a better future for wildlife conservation in this area if the issues associated with human-wildlife conflict are addressed effectively.